Perspectives of syringe services program operators in Michigan on their relationship with substance use treatment: a qualitative study - Molly C. Reid; Samantha J. Harris; Suzanne M. Grieb; Sabrina Gattine; Zekiye Lukco; Brandon Hool; Mary Aguirre; Fernanda Alonso Aranda; Catherine Tomko; Sara Whaley; Brendan Saloner; Sean T. Allen (Harm Reduction Journal)
Abstract Background Substance use treatment (SUT) and harm reduction are often perceived as having distinct goals despite people who use drugs routinely having needs that encompass both services. The co-occurring SUT and harm reduction needs of people who use drugs warrant collaboration between service providers. However, little work has explored such collaborations, or lack thereof. This research explores how SUT providers responded to expanded harm reduction programming from the perspectives of syringe services program (SSP) operators in Michigan. Methods We conducted in-depth, semi-structured interviews with a geographically diverse sample of SSP operators (n = 19) in Michigan during October and November 2021. The interview guide broadly explored the contributing factors to SSP implementation, including SSP relationships with SUT providers. Analyses of transcribed interviews were conducted using an iterative, thematic constant comparison process informed by grounded theory. Results Participants described a range of responses to SSP implementation from SUT providers. Many SSP operators identified significant barriers to effective collaboration with SUT providers due to lack of awareness about harm reduction approaches and stigmatization of drug use. For example, SUT providers were often reluctant to accept free harm reduction supplies (e.g., sterile syringes, naloxone) to offer their clients. Participants also reported difficulties connecting their clients to evidence-based SUT providers. Incremental relationship building and education about the role of harm reduction in recovery were required for effective collaboration between SUT providers and SSPs. Conclusions Tensions between SUT and harm reduction providers may create challenges that impede recovery among people who use drugs. Ensuring SUT and harm reduction providers understand the unique and complementary roles of each approach is necessary to advance the health of people who use drugs.